BEST PRACTICES FOR SUSTAINABLE PRODUCTION CHAIN - Choy Zevallos, Elsa Esther (2015)
The work is a continuation of the subject: “Chain of sustainable production costs and national food security “, which was published in the Journal of Accounting Research Quipukamayoc in the previous edition. This time, it is aimed to develop the best practices to achieve continual improvement in agricultural production chain, which, as noted above, ensures sustainable development with economic and ecological sustainability, social and humanistic justice, where natural processes are integrated with production as well as higher productivity of plants and organic products.The study develops the best environmental friendly practices for sustainable production with organic agriculture, it has a deductive methodological approach of descriptive type, and presents and as a result, a structure of best practices that add value to agricultural production chain under five dimensions: social, ecological, economic, cultural and social responsibility.